Autogenous Chin Block Grafts in the Aesthetic Zone: A 20-Year Follow-Up Case Report - Carlo Maiorana; Susanna Ferrario; Pier Paolo Poli; Mattia Manfredini (Case Reports in Dentistry)
The successful use of osseointegrated implants in the treatment of partial or complete edentulism requires a sufficient bone support. Whenever rehabilitation in atrophic edentulous areas is needed, bone augmentation procedures are recommended. The aim is to provide adequate amount of supporting bone to achieve a prosthetically guided implant placement. This in turn leads to functional and aesthetic improvements that can be maintained on the long term. Bone grafting of the atrophic site can be performed either prior to implant placement or at the time of implantation. Irrespective of the timing, bone augmentation by means of autogenous bone grafts is a reliable technique, as confirmed by several studies. On the other hand, long-term evidence on the use of autogenous chin block grafts in preprosthetic implant surgery is still scarce. Thus, the purpose of the present case is to report the 20-year clinical and radiological outcome of autogenous chin block grafts used to augment a bilateral defect due to agenesis of the upper lateral incisors for implant placement purposes.